2018
DOI: 10.1039/c7ob02783d
|View full text |Cite
|
Sign up to set email alerts
|

Genetically-encoded fragment-based discovery (GE-FBD) of glycopeptide ligands with differential selectivity for antibodies related to mycobacterial infections

Abstract: Accurate identification of tuberculosis (TB), caused by Mycobacterium tuberculosis, is important for global disease management. Point-of-care serological tests may improve TB diagnosis; however, specificities of available serodiagnostics are sub-optimal. We employed genetically encoded fragment-based discovery (GE-FBD) to select ligands for antibodies directed against the mycobacterial cell wall component lipoarabinomannan (LAM), a potent antigen. GE-FBD employed a phage displayed library of 10 heptapeptides, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 30 publications
0
25
0
Order By: Relevance
“…The above differential enrichment (DE) analysis also compared the screen of glycosylated and unmodified libraries and discarded sequences that were equally enriched with and without glycosylation (Figure D). The latter filtering strategy has previously shown to be effective in discovery of peptides that bind to GBP in synergy with glycan . Intersect of the 3 DE analyses yielded 1061 glycopeptides that satisfied all criteria (Figure E).…”
Section: Resultsmentioning
confidence: 94%
See 3 more Smart Citations
“…The above differential enrichment (DE) analysis also compared the screen of glycosylated and unmodified libraries and discarded sequences that were equally enriched with and without glycosylation (Figure D). The latter filtering strategy has previously shown to be effective in discovery of peptides that bind to GBP in synergy with glycan . Intersect of the 3 DE analyses yielded 1061 glycopeptides that satisfied all criteria (Figure E).…”
Section: Resultsmentioning
confidence: 94%
“…We previously demonstrated that genetically encoded fragment‐based discovery (GE‐FBD) in which the glycan fragment is covalently linked to library of ten peptide fragments can minimize challenges of classical genetically encoded peptide libraries, high‐throughput screens, and fragment‐based discovery alone. In several reports, GE‐FBD applied to glycan‐binding proteins yielded peptide–glycan combinations 10‐50 times more potent than the original glycan fragment . In GE‐FBD, the carbohydrate fragment directs the interactions of peptide and target to the CRD and the screening process could identify peptides that provide synergistic binding contributions that enhance overall binding affinity.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…[37] These reactions need to be extremely selective to be suitable for phage or mRNA displayed libraries without damaging the requisite phage particle or nucleic acid tag. [36,38] Of particular note is that even alow-affinity glycan can be used to target the site of binding,t hus increasing the chance of discovering ag lycopeptide with the desired biological activity. [36,38] Of particular note is that even alow-affinity glycan can be used to target the site of binding,t hus increasing the chance of discovering ag lycopeptide with the desired biological activity.…”
Section: Seino Jongkees Is Assistant Professor In the Department Of Cmentioning
confidence: 99%